Pengelolaan Peningkatan Mutu Pembelajaran Numerasi Berdasarkan Hasil Rapor Pendidikan Di SMPN 01 Bengkulu Utara - Wawan Effry Setiawan; Nur Sasongko , Rambat (Manajer Pendididikan, 2023)
The aim of the research is to analyze the management of improving the quality of learning numeracy based on the results of education reports at 01 State Junior High School North Bengkulu. The specific objective is to analyze the planning, implementation and monitoring of improving the quality of learning numeracy. Qualitative descriptive research method, subject to the principal, curriculum representative and science teacher using observation, interview and documentation instruments. Analysis techniques through data reduction, data presentation, and drawing conclusions. The results of the research at the planning stage carried out data-based planning, student-oriented planning, teachers and supporting facilities, as well as numeration sources. The implementation stage is through numeration techniques, physical facilities and numeration facilities, the academic environment and improving the quality of numeracy teachers. Monitoring is in the form of monitoring targets, time intensity, indicators of achievement of program implementation and identification of supporting/inhibiting factors for the program. Through good quality improvement management policies, teacher competence, students' numeracy abilities and the numeracy learning process in schools also increase.